2-(4-Methylanilino)acetohydrazide - Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title molecule, C(9)H(13)N(3)O, the non-hydrogen atoms of the hydrazide group are essentially planar [maximum deviation = 0.028 (1) Å for one of the N atoms]. The mean plane of this group forms a dihedral angle of 83.34 (5)° with the plane of the benzene ring. In the crystal structure, molecules are linked by intermolecular N—H⋯O, N—H⋯N and weak C—H⋯N hydrogen bonds into a two-dimensional network parallel to the ab plane. Additional stabilization is provided by a weak C—H⋯π interaction.